Validasi Metode Analisis dan Penetapan Kadar Encapsulated Retinol Dengan Metode Spektrofotometri UV - Istiqomah, Dewi Aulia; Fauzi, Ahmad (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Retinol is a widely used active anti-aging ingredient in cosmetic products, but it is unstable to light and oxidation. Encapsulation technology enhances its stability and reduces skin irritation, yet complicates its quantitative analysis. This study aims to validate a UV spectrophotometric method for determining the concentration of encapsulated retinol in BPOM-labeled commercial serum preparations. Validation was carried out for linearity, accuracy, intraday precision and interday precision, LOD, and LOQ according to AOAC (2002) and ICH Q2(R1) guidelines. Sample preparation involved sonication to release retinol from its encapsulating matrix prior to measurement. The maximum wavelength was observed at 325 nm using ethanol as solvent. The calibration curve yielded the equation y = 0.139x + 0.0033 with R2 = 0.998, indicating excellent linearity. Recovery ranged from 92-105%, while precision showed %RSD < 2%, confirming high reproducibility. LOD and LOQ were 0.01 ppm and 0.03 ppm, respectively. Specificity evaluation demonstrated that both the standard and sample solution exhibited a maximum peak at 325 nm, whereas the blank serum matrixs showed a distinct peak at 280 nm with no absorbance at the analytical wavelength, confirming the selectivity of the method. Thus, the UV spectrophotometric method was validated and proven suitable for the routine quantification of free retinol released from encapsulated system in commercial skincare serums.